2013
DOI: 10.1590/s1980-57642013dn70100009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a case series of behavioral variant frontotemporal dementia: Emphasis on diagnostic delay

Abstract: INTRODUCTIONDespite many advances in the characterization of the behavioral variant of frontotemporal dementia (bvFTD), the diagnosis of this syndrome poses a significant challenge, while delays or diagnostic mistakes may impact the proper clinical management of these patients.OBJECTIVETo describe the clinical profile at first evaluation of a sample of patients with bvFTD from a specialized outpatient neurological unit, with emphasis on the analysis of the delay between the onset of symptoms and diagnosis.METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…An early and correct identification and evaluation of BPSD are challenges and crucial parts in the clinical approach and management of these disorders. As at the disease onset, BPSD may dominate the clinical picture and may be interpreted as a primary psychiatric disorder, this can delay the proper evaluation and diagnosis of dementia (55). This is an important point as the earlier diagnosis is reached; more families and patients will be able to benefit from the use of appropriate clinical support and possible intervention.…”
Section: Discussionmentioning
confidence: 99%
“…An early and correct identification and evaluation of BPSD are challenges and crucial parts in the clinical approach and management of these disorders. As at the disease onset, BPSD may dominate the clinical picture and may be interpreted as a primary psychiatric disorder, this can delay the proper evaluation and diagnosis of dementia (55). This is an important point as the earlier diagnosis is reached; more families and patients will be able to benefit from the use of appropriate clinical support and possible intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies, including our own, have shown that patients with bvFTD may also manifest with early neuropsychiatric symptoms, such as depression and psychosis [22,23]. Those patients who show only a few core clinical bvFTD features, or primarily present with psychiatric symptoms, are initially often misdiagnosed as having late-onset psychiatric disorders or other neurodegenerative diseases, most often AD [23][24][25][26]. Therefore, misrecognition of symptoms in the early stages of bvFTD frequently leads to diagnostic delay [27][28][29][30].…”
Section: Introductionmentioning
confidence: 85%
“…[15][16][17][18] In other words, later diagnosis of FTD is common in many underrepresented populations. 15,17,19,20 These delays are due to factors at the level of the individual/family, and those at the level of the medical/health system (summarized in Table 1). In preparation for a 2021 externally led Patient-Focused Drug Development meeting on FTD, The Association for Frontotemporal Degeneration and the FTD Disorders Registry collaborated on the FTD Insights Survey, a community-based online survey of nearly 1800 diagnosed patients, care partners, and family members designed to better TA B L E 1 Individual and clinical barriers to FTD diagnosis in diverse populations.…”
Section: Clinical Presentation and Diagnostic Challenges In Diverse P...mentioning
confidence: 99%